Computer attitude in psychiatric inpatients. - Weber, Bernhard; Schneider, Barbara; Hornung, Stefan; Wetterling, Tilman; Fritze, Jürgen (Computers in Human Behavior, 2008)
Negative computer attitude has been shown to be a possible co-variable in computerized examinations of psychiatric patients, affecting patient-computer interaction as well as reliability and validity of assessments. It remains still uncertain if the psychological construct of computer attitude can be dependably measured in acute psychiatric inpatients or whether it is impeded by the effects of mental illness. For that reason a German translation of the Groningen Computer Attitude Scale (GCAS) was evaluated in 160 acute psychiatric inpatients under naturalistic conditions. General test criteria (internal structure, item analysis, internal consistency, split half reliability) to a large extent corresponded to those formerly found in healthy subjects and psychiatric outpatients. The mean GCAS score was calculated as 56.2±10.8 points and a significantly better computer attitude was found in male, better educated and younger patients. Some diverging correlation patterns were found in diagnostic subgroups, indicating a possible minor impact of mental disorder on computer attitude. Overall, the GCAS was found to be a suitable instrument for measuring computer attitude in acute psychiatric inpatients. It should be used in identifying patients with a negative attitude to computers in order to ensure reliability and validity of computerized assessment. Copyright (c) 2008 Elsevier Ltd.